Wakalah: Legal Analysis and Its Aspects - Simanungkalit, Jason Aaron Riado; Pradini, Yustia Okta; Allariksyah, M. Satria; Heryadi, Raihan; Rahmawati, Esa; Mahipal, Mahipal (PT FORMOSA CENDEKIA GLOBAL, 2024)
Wakalah is a concept in Islamic law that allows a person to appoint a representative or agent to carry out tasks or transactions on their behalf. A wakalah agreement is an agreement where the first party gives power or mandatory to the second party. It is impossible for each individual to handle all matters only by themselves. Therefore, Allah SWT has established rules about how the wakalah contract can be carried out, providing benefits for us. Wakalah comes from words “wakalah-yakilu-waklan”, which means submission or giving authority to a representative. Wakalah can be interpreted as handing over tasks that a person can carry out independetly to another person, so that the person carries out these tasks throughout his life. This paper aims to provide an in-depth analysis of wakalah from the perspective of Islamic law, as well as identifying the key aspects involved.